MAIN TRENDS IN THE DEVELOPMENT OF BIOECONOMIC STRATEGIES IN AGROINDUSTRY: A SYSTEMATIC LITERATURE REVIEW - Muflihah Ramadhia; Imam Santoso (Jurnal Ekonomi, 2023)
Bioeconomics is an emerging concept and has not been given a generally accepted definition. Bioeconomic strategy tries to consider every aspect of this emerging concept from different perspectives depending on the country, region, or organization that publishes it. Therefore, each strategy has its advantages depending on the economic, geomorphological, social, environmental, and technological conditions of each country. In this review, attempts are made to address key trend areas of bioeconomic strategies through a systematic literature review. PRISMA analysis is used to review the literature on key trend areas of bioeconomic strategies. Review articles address this topic in two major scientific literature databases, namely Scopus and AgEcon. Using a repeatable search process to identify relevant studies in the literature, only 68 publications that met the eligibility criteria were included in the review. The results showed that the movement of the main trends of the Bioeconomic Strategy in agro-industry 2013-2022 was observed as well as the economic and technological development of each country to show its superiority. The transition to a successful bioeconomy model requires the participation of the whole society because a sustainable society as a whole requires sustainable and environmentally responsible solutions. The study concludes that management with global coordination and training for stakeholders is necessary for the successful implementation of bioeconomic strategies in agro-industry.